Tipos de maltrato infantil y su relación con los tipos de infracciones en adolescentes recluidos en un centro juvenil de Trujillo - Muñoz Moreno, Juan Manuel (2014)
General Objective: Determining that there is relationship between typesof child abuse and types of violations in detained teenagers in a YouthCentre of Trujillo. Material and Methods: A descriptive, correlational study and cross sectional were carried out in 117 detained teenagers in the center, who were applied the Childhood Trauma QuestionnaireSurvey-Short Form (CTQ-SF). All of them, only 86 met the inclusion criteria, constituting my test sample. Results: Physical and emotional abuses, physical and emotional neglects are directly related to infractions against property; whi le sexual abuse is inversely related. Emotional abuse is directly related to infractions against life, body and health. Sexual abuse is directly related to infractions against sexual freedom; while physical, emotional abuses and physical neglect are inversely related. Sexual abuse is directly related to infractions for illegal possession of arms, while emotional abuse is inversely related. Conclusion: All types of child abuse are related to at least one of the types of violation found.